Education on preparation for exclusive breastfeeding through face-to-face classes for pregnant women in the third trimester to increase breastfeeding self-efficacy - Winarsih, Winarsih; Revika, Era (Universitas Jenderal Achmad Yani Yogyakarta, 2025)
Background: Mother's milk makes children have potential, have stable emotions, are spiritually mature, and have good social development. It is hoped that educational classes will be able to become a means of obtaining information, knowledge and become a means of discussion about the problems faced by breastfeeding mothers and will further help increase self-efficacy in providing exclusive breastfeeding to babies.Objective: This study aims to analyze differences in Breastfeeding Self-Efficacy in third trimester pregnant women before and after being given education on preparing for exclusive breastfeeding through face-to-face mother classes.Method: The design in this study uses a quasi-experiment method with a one group pre test - post test design model. The sample in this study is the total population, namely all pregnant women in the third trimester who are willing to be research respondents from the time the education begins until it is completed. Totaling 30 respondentsResults: The results of the paired sample t-test analysis show that the p-value is <0.012. So it can be concluded that the p-value is 0.012 < 0.05.Conclusion: There is a significant effect of providing education on preparation for exclusive breastfeeding through face-to-face classes for pregnant women on breastfeeding self-efficacy